REGULATORY CONSOLIDATION OF THE PRESUMPTION OF LEGITIMACY OF ACTIONS AND CLAIMS OF A PERSON (ON THE EXAMPLE OF THE LAW OF UKRAINE «ON ADMINISTRATIVE PROCEDURE» AND THE TAX CODE OF UKRAINE) - VDOVICHEN, VITALIY (Ehrlich's Journal, 2024)
Abstract. In the article, the author studies the statutory consolidation of the principle of presumption of legitimacy of actions and claims of an individual in administrative and tax procedures, using the rules of the Law of Ukraine «On Administrative Procedure» and the rules of the Tax Code of Ukraine. The author determines that the laws on administrative procedure are aimed primarily at protecting an individual from arbitrariness on the part of the administration. However, they also determine the actions of public servants in terms of the procedural algorithm for consideration of applications, complaints, and activities initiated by an administrative body, or consideration of complaints in the pre-trial procedure. The author establishes that the importance of principles in the implementation of both administrative procedure and tax procedure is manifested in their law enforcement effect through enshrining in legislation. Therefore, the article examines the norms of the Law of Ukraine «On Administrative Procedure» which provide that the presumption of legitimacy of actions and claims of a person means that actions and claims of a person are legitimate until otherwise proven during consideration and/or resolution of a case; doubts about the legitimacy of actions and claims of a person arising from ambiguous (multiple) interpretation of a legal norms should be interpreted by an administrative authority in favour of their legitimacy. The author also examines the norms of the Tax Code of Ukraine: the presumption of interpretation of tax legislation in favour of the taxpayer, the presumption of illegality of the contested decision, the presumption of tacit consent of the supervisory authority of the highest level with the arguments and claims of the complainant. It is determined that there are two approaches to understanding the category of «presumption in the theory of law the first approach is as a special legal construct which exists in an objective form and is a normative prescription», a legal rule of «nonstandard nature», «an assumption enshrined in a legal rule» (direct presumption); the second approach as a legal phenomenon that is not formalised (not directly enshrined) in the legal norms, but is derived by logical inference in the process of interpreting legal norms, i.e. in the process of their law application – «logical inference», «assumption», «certain assumption» (indirect presumption). The author proves that the principle of presumption of legitimacy of actions and claims of a person is reduced to the following: a) actions and legal position of a citizen who applies to an administrative authority are considered legitimate until otherwise established by a decision of the body (official) competent to consider an administrative case; b) the decision of an administrative authority should not be based on assumptions, and all doubts about the legitimacy of the citizen's position should be interpreted in his/her favour. The practical significance of the principle of presumption of legitimacy of actions and claims of a person in both administrative procedure and tax procedure is as follows: it helps the administrative authority to achieve adequate application of substantive law; this principle, together with others, provides minimum unified standards for ensuring the exercise and protection of the rights and legitimate interests of participants in both administrative procedure and tax procedure; it serves as a guideline for assessing the legality of administrative acts adopted, procedural decisions and procedural actions taken.